PERANAN KOMITE AUDIT DAN DEWAN PENGAWAS SYARIAH TERHADAP KUALITAS LAPORAN KEUANGAN (Studi Kasus pada BPRS di Jawa Timur) - Lestari, Iin Fitri; Oktaviana, Ulfi Kartika (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2020)
AbstractAudit Committee and Sharia Supervisory Board are the parts of the organization which help to manage the financial reports of BPRS with high quality. The aim of this research is to find out the influences of the Audit Committee’s and Sharia Supervisory Board’s role toward the quality of financial reports especially in BPRS of east java. This study applies a quantitative approach, focused on the associative type. Moreover, the sample is taken by using a purposive sampling method. The objects are 15 institutions of BPRS in east java which are registered in OJK and BI, each BPRS is given a questionnaire and it was returned around 38 questionnaires. After the data was collected, it was directly processed and analyzed by using a statistical application that is SPSS 16. The variable of the research involves 7 indicators of Audit Committee responsibilities, 9 indicators of DPS supervision activities, and 9 indicators of financial report quality. Consequently, the research result provides that according to a partial test, there is a good effect between the roles of the audit committee towards the quality of financial reports. Based on a partial test, there is a bad effect between DPSs’ roles towards the quality of financial reports. According to the simultaneous test, Audit Committee together with DPS influence the quality of financial reports